Food-grade High Internal Phase Pickering Emulsions: Food-grade Solid Particles, Stabilization Mechanisms and Application in Encapsulating Probiotics - Yaxin YIN; Qirui LIU; Zhicheng WANG; Qiwei DU; Tao ZHANG; Daodong PAN; Maolin TU (Shipin gongye ke-ji)
Probiotics are live microorganisms that provide various health benefits, such as enhancing immune function and regulating gut microbiota. However, their high sensitivity to environmental conditions makes them prone to inactivation during production, storage, and use. The microstructure of high internal phase Pickering emulsions (HIPPEs) droplets can accommodate probiotics in the oil phase, protecting them from contact with water and thereby improving their survival rate. Here, the various types of food-grade solid particles used to stabilize Pickering emulsions and their mechanisms are firstly reviewed in this paper, including wetting properties at the interface, steric hindrance mechanisms, and three-dimensional network mechanisms. Furthermore, the application of HIPPEs in probiotic encapsulation is elaborated, focusing on the characteristics and differences of various types of HIPPEs in terms of probiotic encapsulation and delivery. Finally, the development prospects and future research directions of HIPPEs are discussed, aiming to provide a theoretical basis and new ideas for the development of probiotic encapsulation technologies.